Controlling Resistance Switching Polarities of Epitaxial BaTiO3 Films by Mediation of Ferroelectricity and Oxygen Vacancies. (24th April 2015) - Li, Ming; Zhou, Jian; Jing, Xiaosai; Zeng, Min; Wu, Sujuan; Gao, Jinwei; Zhang, Zhang; Gao, Xingsen; Lu, Xubing; Liu, J.‐M.; Alexe, Marin
<x xml:space="preserve">Abstract</x> In this work, the observations of different resistive switching polarities of epitaxial BaTiO3 (BTO) thin films fabricated by pulsed laser deposition are reported. The BTO films with various ferroelectric states and oxygen vacancy (VO) concentrations are achieved by carefully controlling the oxygen pressure during the depositions. For films with no ferroelectricity and high VO concentrations, the resistance will change from a low resistance state (LRS) to a high resistance state (HRS) during a positive voltage cycle (0 → 3 → 0 V), and from a HRS to a LRS during a negative voltage cycle (0 → −3 → 0 V). However, completely opposite RS polarity is observed for the films with weak ferroelectricity and intermediate VO concentrations. Such RS behaviors and polarity can be hardly observed or negligible for the films with good ferroelectricity and nearly free of VO. It is proposed that the unique resistance switching polarities of BTO films are attributed to the competition between the ferroelectricity and oxygen vacancy migration dynamics. Results clarify the complex RS mechanisms in the BTO films, and address the competing ferroelectricity and VO migration in modulating the RS behaviors of ferroelectric oxide‐based resistive memory devices.